Brillouin gain spectrum dependence on large strain in perfluorinated graded-index polymer optical fiber - Hayashi, Neisei; Mizuno, Yosuke; Nakamura, Kentaro (Optics express, 2012)
We investigate the dependence of Brillouin gain spectra on large strain of > 20% in a perfluorinated graded-index polymer optical fiber, and prove, for the first time, that the dependence of Brillouin frequency shift (BFS) is highly non-monotonic. We predict that temperature sensors even with zero strain sensitivity can be implemented by use of this non-monotonic nature. Meanwhile, the Stokes power decreases rapidly when the applied strain is > ~10%. This behavior seems to originate from the propagation loss dependence on large strain. By exploiting the Stokes power dependence, we can probably solve the problem of how to identify the applied strain, when the identification is difficult only by BFS because of its non-monotonic nature.